A novel technique for dynamic shear testing of bulk metals with application to 304 austenitic stainless steel. (November 2020) - Jia, B.; Rusinek, A.; Pesci, R.; Bernier, R.; Bahi, S.; Wood, P.
Graphical abstract: Highlights: New shear specimen designed for dynamic tests using SHPB device. Deformation behavior of 304 ASS investigated over a wide range of strain rates from 0.001 s −1 to 38700 s −1 . Ultra-high strain rates above 10 4 s −1 achieved. Simple shear stress state with low stress triaxiality and Lode angle parameter obtained. Correction coefficient method for accurate shear stress-shear strain relations measurement. Abstract: This paper describes a new single-shear specimen (SSS) and method to characterize the dynamic shear behavior of bulk metals using a traditional Split Hopkinson Pressure Bar (SHPB). By this method, the shear behavior of materials can be tested conveniently over a wide range of strain rates within 10 5 s −1 . This technique was applied to a 304 austenitic stainless steel (ASS) under shear strain rates from 0.001 s −1 to 38700 s −1 at room temperature. Based on finite element (FE) simulations, it was found that the deformation of the specimen shear zone was dominated by shear stress/strain components. Stress state parameters represented by stress triaxiality η and Lode angle parameter θ - were found very close to zero, indicating a deformation mode of simple shear. Besides, an obvious gap existed between the local deformation behavior in the specimen shear zone and the macroscopic stress-strain relations measured by the strain gauges on the SHPB bars. A correction coefficient method was adopted to extract the real shear behavior from the experimentally obtained force-displacement data. Through comparisons between the tested and simulated stress-strain curves, a good agreement was obtained.